Reliability of Sensorimotor Control Tests in Individuals with Adolescent Idiopathic Scoliosis - Alexandros Kastrinis; Nikolaos Strimpakos; George A. Koumantakis; Dionysios Tzatzaliaris; Marianna Oikonomaki; Evangelos Theodosopoulos; Evangelia Skaftourou; Maria Tsekoura; Asimakis K. Kanellopoulos; Eleni Nomikou; Zacharias Dimitriadis (Muscles, 2024)
Background: The presence of sensorimotor control deficits in adolescent idiopathic scoliosis compared to typically developed adolescents is supported by the literature but lacks reliability studies for assessment in this population. This study aimed to assess the reliability of eight sensorimotor control tests, in terms of static and dynamic balance, joint position sense (JPS) tests of the extremities and the spine, and a functional upper extremity proprioceptive test in adolescent idiopathic scoliosis subjects. Methods: Sixty adolescent idiopathic scoliosis subjects were divided into four groups. Each group underwent two tests by the same examiner, repeated at 15 min intervals. Reliability was measured using the intraclass correlation coefficient (ICC), standard error of measurement (SEM), and smallest detectable difference (SDD). Results: The results showed high reliability for the upper extremity functional proprioception test, for the dynamic and static balance test, and for the spinal lateral flexion joint position sense test in both directions. On the other hand, the shoulder external rotation, knee extension, elbow flexion, and spinal flexion joint position sense tests demonstrated poor reliability in adolescent idiopathic scoliosis subjects. Conclusions: Therapists are recommended to use the functional upper extremity proprioception test, the Fukuda test, the static balance test using a force footplate, and the spinal lateral flexion joint position sense test for assessing treatment progress in this population.